Psicología Social. Algunas claves para entender la conducta humana. Anastasio Ovejero - Crespo Suárez, Eduardo (Anales de Psicología / Annals of Psychology, 2010)
This book has been conceived as a treatise on social psychology not only for students but also for the general public. It aims to show what psychosocial research can teach us about the main problems of our time. The author takes a critical approach, based on extensive and updated information.